2021
DOI: 10.3390/nu13030770
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Neurodegeneration: Correlation between Nutraceutical Treatment and Animal Model

Abstract: Retinal diseases can be induced by a variety of factors, including gene mutations, environmental stresses and dysmetabolic processes. The result is a progressive deterioration of visual function, which sometimes leads to blindness. Many treatments are under investigation, though results are still mostly unsatisfactory and restricted to specific pathologies, particularly in the case of gene therapy. The majority of treatments have been tested in animal models, but very few have progressed to human clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…This is in line with previously published data [8], which demonstrated that saffron treatment reduces gliosis processes better than PBM treatment alone. Specifically, we confirmed that PBM exposure in neurodegeneration requires to be finely administrated, probably more shortly [33] in comparison with saffron, whose positive effect on Muller cells was also underlined in other glial-dependent retinal dystrophies, such as in Fischer rats [26]. Furthermore, we confirmed that PBM treatment barely mitigates neurodegenerative processes if provided immediately after LD [33].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This is in line with previously published data [8], which demonstrated that saffron treatment reduces gliosis processes better than PBM treatment alone. Specifically, we confirmed that PBM exposure in neurodegeneration requires to be finely administrated, probably more shortly [33] in comparison with saffron, whose positive effect on Muller cells was also underlined in other glial-dependent retinal dystrophies, such as in Fischer rats [26]. Furthermore, we confirmed that PBM treatment barely mitigates neurodegenerative processes if provided immediately after LD [33].…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, treatments applied might compete in the intracellular calcium flux. Furthermore, PBM and saffron neuroprotection might be affected by the physio-pathological context, which requires a different balance among antioxidants, trophic factors, or anti-inflammatory molecules [26]. Accordingly, a biphasic dose-response related to low-level light therapy was suggested [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex structural and functional nature of the retina makes such tissue extremely vulnerable to aberration due to any kind of injury [3,5]. In fact, the retina has to respond to a series of environmental insults to whom is commonly exposed, including light-induced stress and oxidative stress and, because of the high metabolic activity of the tissue, it is particularly susceptible to variation of oxygen and nutrient availability [5].…”
Section: Retina and Retinal Degenerationmentioning
confidence: 99%
“…Globally, in 2015, it was estimated that blindness and moderate/severe vision impairments affect more than 36 and 216 million of people, respectively, and the number has raised along with the increase in population and age [1,2]. Retinal neurodegenerative diseases, including diabetic retinopathy, DR, retinitis pigmentosa, RP, age-related macular degeneration, AMD, or glaucoma, are the most frequent causes of irreversible vision impairment and blindness worldwide [3,4]. Despite the high economic and social impact of vision impairment and blindness, there are no cures for retinal neurodegenerative pathologies [4,5].…”
Section: Introductionmentioning
confidence: 99%